The Factor of Politeness in Unfavorable Book Reviews - Vardanyan, Irina (Armenian Folia Anglistika, 2008)
The article offers a thorough examination of the genre of book review and analysis of the means used by the critic to make unfavorable reviews with special reference to the factor of politeness.The author conducts a comparative analysis of the similarities among the unfavorable book reviews in English and Russian as well as their culture-bound differences.